2019
DOI: 10.1016/j.compositesb.2019.107334
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties of 3D multi-layer wrapping braided composite: Progressive damage analysis

Abstract: An experimental and numerical study on mechanical properties and damage behavior of 3D multi-layer wrapping braided composite under axial tensile load is presented. The braiding process of this material is introduced and its tensile properties are obtained in tensile tests. Numerical simulations employ periodical boundary conditions, with interface elements between yarns and matrix added to improve the accuracy of prediction. 3D Hashin-type criteria and Von-Mises stress criterion are employed as damage initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…23,24 Braided fabric strengthened composites have better mechanical characteristics compared to conventional woven fabric strengthened composites. 25 Xiaopei Wang 26 carried out damage behaviour study on 3D multilayer wrapping braided composites. They concluded that for the braided composites there is no compressive cracking in yarn-matrix, compressive fibre failure and shear failure in fibre-matrix.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Braided fabric strengthened composites have better mechanical characteristics compared to conventional woven fabric strengthened composites. 25 Xiaopei Wang 26 carried out damage behaviour study on 3D multilayer wrapping braided composites. They concluded that for the braided composites there is no compressive cracking in yarn-matrix, compressive fibre failure and shear failure in fibre-matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In numerical simulations, once a component of material is damaged according to the aforementioned failure criteria, the corresponding elastic modulus at the relevant integration point is reduced to simulate the damage. In this study, the scheme of material-performance degradation developed based on literature 26,27 was adopted. The stiffness-degradation coefficients corresponding to respective failure modes are listed in Table 4.…”
Section: Progressive Damage Modelmentioning
confidence: 99%
“…[21] and Wang et al. [22] presented a meso-scale FE model, in which the interface behavior is modeled by cohesive zone model with cohesive elements, to simulate the progressive damage evolution of 3 D braided composites. Sharma et al.…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al [18], Lu et al [19] and He et al [20] proposed a meso-scale finite element model considering the interface debonding to investigate the nonlinear mechanical behavior of 3 D braided composites under uniaxial tension. Zhang et al [21] and Wang et al [22] presented a meso-scale FE model, in which the interface behavior is modeled by cohesive zone model with cohesive elements, to simulate the progressive damage evolution of 3 D braided composites. Sharma et al [23] established an image-based model to determine the elastic properties of 3 D carbon/carbon composites.…”
Section: Introductionmentioning
confidence: 99%